Deploying social robots in museum settings: A quasi-systematic review exploring purpose and acceptability. (23rd December 2021) - Gasteiger, Norina; Hellou, Mehdi; Ahn, Ho Seok
Social robots are increasingly used within public spaces, including museum settings. This quasi-systematic review identifies and synthesizes the evidence on social robots that have recently been deployed in museum settings. It specifically focuses on their intended purpose, their acceptability and factors important for successful human–robot interaction in this setting. Four databases (PsycINFO, SCOPUS, ACM Digital Library and IEEE Xplore) were systematically searched to retrieve literature published within the last 10 years on human–robot interaction studies with social robots deployed in museum settings. Due to the heterogeneous nature of the studies, qualitative and quantitative findings were summarized. A total of 604 items were identified, of which 12 were included in the review. Robots in 11 studies were physical and 1 was an embodied conversational agent presented as a virtual robot. In 75% of the studies ( n = 9), the purpose of the robots was to act as museum guides, while in 17% ( n = 2) they entertained visitors and in 8% ( n = 1) the robot taught visitors in a museum outreach programme. Overall, many of the robots were found to be acceptable for use within museum settings. Three main themes for successful social human–robot interaction were evident across the findings: (1) facial expressions, (2) movement and (3) communication and speech. There is a great opportunity for social robots to be deployed within museum settings, as guides, educators, entertainers or a combination thereof. State-of-the-art methods have led to the development of museum robots that are more capable of social interaction; however, more work is required to develop speech capabilities that work in the 'wild'. Future work should combine the factors that have been identified within this review to improve human–robot interaction.